Effect of Fluctuating surface heat and mass flux on natural convection flow along a vertical flat plate - Hussain, Sharmina; Roy, Nepal Chandra; Hossain, Md. Anwar; Saha, Suvash Chandra (© 2015 Hindawi Publishing Corporation, 2016)
This article was published in the Mathematical Problems in Engineering [ © 2015 Sharmina Hussain et al. ] and the definite version is available at :http://dx.doi.org/10.1155/2015/258016. The Journal's website is at: https://www.hindawi.com/journals/mpe/2015/258016/